5x-(-5x-1)=-8

Simple and best practice solution for 5x-(-5x-1)=-8 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5x-(-5x-1)=-8 equation:


Simplifying
5x + -1(-5x + -1) = -8

Reorder the terms:
5x + -1(-1 + -5x) = -8
5x + (-1 * -1 + -5x * -1) = -8
5x + (1 + 5x) = -8

Reorder the terms:
1 + 5x + 5x = -8

Combine like terms: 5x + 5x = 10x
1 + 10x = -8

Solving
1 + 10x = -8

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-1' to each side of the equation.
1 + -1 + 10x = -8 + -1

Combine like terms: 1 + -1 = 0
0 + 10x = -8 + -1
10x = -8 + -1

Combine like terms: -8 + -1 = -9
10x = -9

Divide each side by '10'.
x = -0.9

Simplifying
x = -0.9

See similar equations:

| 7x+2=-3+4x+23 | | 11x+2=-24 | | 9v+10=v+9 | | 3.5*2= | | x-19=23 | | 5d+8=53 | | 4x+9-7x=-6 | | 90-x=3/4(180-x)-60 | | 4x+9-7x=-9 | | 0.75=w+2/5 | | (x^2-11)/(2x-1) | | (3/4)x-(7/12)=1 | | 11x-4x=27 | | z/2+1+3/2 | | 3(6x+3)=27 | | 5(2x-4)-(3x+1)=2 | | 9+1/9h=9 | | -6=x/3+4 | | 4x+6+8=3 | | 8(2.4r-3.1s)-6(10-4.3s)= | | x^2+4xy-4y^2-9=0 | | 5+22a=2+10/22 | | 1/4c+2=8 | | 8/4=(6)(0) | | -.2(x+10)-.25(x-4)=x+8 | | 6(X+2)-7=18 | | 0.7t=0.3+0.4t | | 4x-2=9x+1 | | -9x+12+4(3x-3)=7(x-2)-14 | | -6=x/3 | | -11.2+4(2.1+q)=8 | | -5(5x+5)-4+8x= |

Equations solver categories